Organic fertilization in nopalitos in the central area of Tamaulipas, Mexico - Reyna-Cabrera, José Gerardo; Almaguer-Sierra, Pedro; Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Sánchez-Reyes, Uriel Jeshua; González-Gaona, Othón Javier (Ecosistemas y Recursos Agropecuarios, 2024)
The production of nopalito, Opuntia ficus-indica (L.) MILL., was analyzed using two varieties, Villanueva (V) and Copena-V1 (C); two densities, 10 plants m2 (D10) and 20 plants m2 (D20); and two organic fertilizers, worm humus (H) and sheep manure (O). The experimental design consisted of a 2*2*3 factorial arrangement (two varieties, two planting densities and three types of fertilization) in three random blocks, with four treatments, three replicates each, 36 experimental units, considering control units without fertilizer (T). The O/V/D20 treatment produced the largest number of nopalitos, 508; the H/V/D10 treatment had the lowest production, 110 nopalitos. The treatment with the highest production in fresh weight was O/C/D10, 60.6 t ha-1. The H/C/D20 treatment had the lowest yield with 30 t ha-1. The MANOVA test showed significant differences (p
Keywords: self-consumption; sheep manure; orchard; earthworm humus; Opuntia ficus-indica